The jumbie god's revenge - Baptiste, Tracey (The jumbies, 2021)
"Huracan summons the wind and rain and wields lightning like a sword. He doesn't miss and he never falters. He will destroy everything in his path if he desires. When an out-of-season hurricane sweeps through Corinne's seaside village, she knows it's not an ordinary storm. At first Corinne believes Mama D'Leau, the powerful and cruel jumbie who rules the ocean, has caused the hurricane. Then an even more ferocious storm wrecks the island, sending villagers fleeing their houses for shelter in the mountains, and Corinne discovers the chaos wasn't caused by a jumbie, but by an angry god, Huracan. Corinne, with the help of her friends and even some of her enemies, must race against time to find out what has angered Huracan and try to fix it before her island home is destroyed forever."